2004
DOI: 10.1095/biolreprod.103.025536
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Maturation of Primate Testis by Xenografting into Mice1

Abstract: Testicular maturation and sperm production throughout the life of the male form the basis of male fertility. It is difficult to elucidate the intricate processes controlling testicular maturation and spermatogenesis in primates in vivo due to the long time span required for sexual maturation and also to the lack of accessible in vitro or in vivo models of primate spermatogenesis. Ectopic xenografting of neonatal testis tissue into mice provides an accessible model to study and manipulate the propagation and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
148
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(162 citation statements)
references
References 13 publications
10
148
1
3
Order By: Relevance
“…Furthermore, we found that the 14-month-old WT monkey-derived testis xenografts collected 12 months after the implantation (with an equivalent age of 14 + 12 = 26 months; Figure 1F) showed large-diameter seminiferous tubules and mature sperm, whereas natural testicular tissues obtained from the 27-month-old TG monkey before xenografting showed seminiferous tubules of small diameters, indicating their relatively immature differentiation ( Figure 1G and Supplementary information, Figure S1). This finding was consistent with a previous study by Honaramooz et al [3], in which comparison was made between the seminiferous tubules in the xenografts and those in natural monkeys of similar ages. Taken together, these data suggest that testicular tissue development is accelerated in the xenografts.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we found that the 14-month-old WT monkey-derived testis xenografts collected 12 months after the implantation (with an equivalent age of 14 + 12 = 26 months; Figure 1F) showed large-diameter seminiferous tubules and mature sperm, whereas natural testicular tissues obtained from the 27-month-old TG monkey before xenografting showed seminiferous tubules of small diameters, indicating their relatively immature differentiation ( Figure 1G and Supplementary information, Figure S1). This finding was consistent with a previous study by Honaramooz et al [3], in which comparison was made between the seminiferous tubules in the xenografts and those in natural monkeys of similar ages. Taken together, these data suggest that testicular tissue development is accelerated in the xenografts.…”
supporting
confidence: 93%
“…The testis tissue from young mammals, including mice and monkeys, is capable of undergoing complete spermatogenesis in xenografts, and sperms obtained from monkey testicular tissue xenografts have yielded monkey blastocysts after intracytoplasmic sperm injection (ICSI), although no successful production of primates has been reported [2][3][4]. Achieving the latter is important because of its potential implication for restoring fertility of young cancer patients undergoing radiotherapy and chemotherapy.…”
mentioning
confidence: 99%
“…For instance, it can advance the initiation of spermatogenesis in primates, which otherwise have long pre-pubertal periods. The grafted primate testis tissue fragments showed accelerated maturation, and fertilization-competent sperms were produced upon xenograft in host mice [15]. In addition, the use of small experimental animals should facilitate any experimental manipulations like local or systemic administration of hormones or factors to the recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Successful xenografts of fresh and cryopreserved testicular tissue have been reported in a variety of species, including: mouse, 26,27 hamster, 28 rabbit, 29 pig, 30 goat, 26 sheep, 26,31 cattle, 32,33 cat, 34 horse 35 and nonhuman primates. 36 Although the risk of retroviral genetic contamination does exist using this xenograft model, consistent graft recovery and complete spermatogenesis have made this model a valuable tool for animal reproductive and toxicology studies.…”
Section: Testis Xenograft Transplantation Modelmentioning
confidence: 99%
“…37 This finding seen with human testis xenografts is similarly seen in animal studies where xenografts made from immature testis tissue had better survival and accelerated maturation once transplanted. 36 For still unknown reasons, mature testis tissue grafts do not support germ cell differentiation as well as immature testis tissue grafts in xenograft models. 38 To further demonstrate this finding, Yu and colleagues 39 transplanted fetal (20-26 weeks) human testicular tissue subcutaneously onto an immunodeficient nude mouse and demonstrated that the xenograft could survive for more than 135 days.…”
Section: Testis Xenograft Transplantation Modelmentioning
confidence: 99%